Emerging trends and perspectives on nano-fertilizers for sustainable agriculture - Ankush Goyal; Sachin S. Chavan; Rajendra A. Mohite; Israr A. Shaikh; Yogesh Chendake; Dadaso D. Mohite (Discover Nano)
Abstract The intensifying global demand for agricultural products has been met with the excessive use of conventional fertilizers, leading to significant environmental pollution, soil and water degradation, and public health concerns. This challenge has been further exacerbated by the pressures of globalization, necessitating the adoption of more sustainable and efficient farming practices. As a promising solution to these issues, nanotechnology has been explored for its innovative approaches to enhance nutrient delivery and reduce environmental impact. In this review, the potential of various nano-fertilizers—including nano-NPK, nano-nitrogen (N), nano-phosphorous (P), nano-potassium (K), nano-iron (Fe), hydroxyapatite (HAP)-modified urea nanoparticles, and nano-zeolite composite fertilizers—has been investigated for improving crop productivity and sustainability. The applications in key crops such as wheat, potato, maize, and rice have been analyzed, with significant yield improvements reported: 20–55% for wheat, 20–35% for potato, 20–40% for maize, and 13–25% for rice. Additionally, grain yield enhancements of 20–55% for wheat, 22–50% for maize, and 30–40% for rice have been observed. It has been emphasized that the optimization of nano-fertilizer concentrations and application methods is crucial to ensure plant health and environmental safety. The transformative role of nano-fertilizers in advancing sustainable agriculture to address global food security challenges has been underscored.